Un réseau national de plantations comparatives pour évaluer les vergers à graines français de Douglas A network of comparative trials for testing French Douglas-fir seed orchards - PHILIPPE, Gwenaël ; MATZ, Stéphane ; BASTIEN, Jean-Charles ; ARCHEVEQUE, Guylaine ; GIRARD, Sabine ; MUSCH, Brigitte (Sciences, Eaux & Territoires, 2012)
Afin de répondre aux enjeux économiques et écologiques de la production de bois en France, les sylviculteurs ont besoin de variétés productives, durables et résistantes aux aléas climatiques. Séduits par les nombreuses qualités du Douglas, nombreux sont les forestiers français qui se sont appropriés ce résineux, devenu la seconde essence la plus utilisée pour le reboisement. Focus sur le réseau national d'essais coordonné par Irstea qui permettra de définir les conditions d'utilisation des huit vergers à graines français de Douglas et d'orienter le choix des reboiseurs dans un contexte climatique en évolution. The recent release of six new Douglas fir seed orchard varieties has motivated the establishment of a network of comparative trials including the eight French Douglas fir orchards. It aims at studying improved variety plasticity and performances (growth, form) in comparison with a control from the natural range. Altogether, 27 tests were planted between 2009 and 2011 at a large range of sites: regions where Douglas fir is widely cultivated, high elevation and "climatic margins". This network will enable the partners (Irstea, ONF, INRA, CNPF) to provide forest owners with recommendations. Useful information has already been obtained for lateness of bud flushing and, therefore, sensitivity to spring frost.